Defining unmet clinical need across the pathway of brain tumor care: a patient and carer perspective - Sage W; Fernández-Méndez R; Crofton A; Gifford MJ; Bannykh A; Chrysaphinis C; Tingley E; Bulbeck H; Brahmbhatt M; Pickard JD; Walter FM; Brodbelt A; et al. (Cancer Management and Research, 2019)
William Sage,1 Rocío Fernández-Méndez,1 Anna Crofton,2 Michael J Gifford,3 Alexey Bannykh,3 Constantinos Chrysaphinis,4 Emma Tingley,4 Helen Bulbeck,5 Mita Brahmbhatt,1 John D Pickard,1 Fiona M Walter,6 Andrew Brodbelt,2 Stephen J Price,1 Alexis J Joannides1 1Department of Clinical Neurosciences, University of Cambridge, Cambridge, UK; 2Department of Neurosurgery, The Walton Centre, Liverpool, UK; 3Mountain Hare Consulting, London, UK; 4The Brain Tumour Charity, Farnborough, UK; 5Brainstrust, Cowes, Isle of Wight, UK; 6Primary Care Unit, Department of Public Health and Primary Care, University of Cambridge, Cambridge, UK Objective: The aim of this study was to determine the experience of patients with brain tumors and their carers across distinct parts of their treatment pathway and identify their views on potential service gaps in need of addressing.Methods: A structured survey was administered at patient workshops across the UK and online through a charity newsletter. Answers to closed questions were analyzed using descriptive statistics, and open questions were examined using techniques of inductive content analysis.Results: A total of 136 survey responses were received, representing patients with a variety of diagnoses and geographical locations (30 counties). There was a wide range of opinions on the provision of current neuro-oncology services. Key themes identified included a perceived lack of information provision, a gap in postdischarge psychological and neuropsychological supports, and an unmet willingness for involvement in research.Conclusion: This national survey enhances our knowledge of current patient and carer experience within neuro-oncology services. A number of areas of unmet clinical need are highlighted providing a basis for informing future patient-centered service improvements and research. Keywords: patient experience, brain cancer, brain tumors, neuro-oncology pathway